The Impact of Consuming Healthy Cookies Enriched with Linoleic Acid for Two Weeks on Blood Fatty Acid Profiles (P08-099-19). (24th October 2019) - Cole, Rachel; Angelotti, Austin; Belury, Martha
Abstract: Objectives: Increasing linoleic acid (LA) in the diet through supplementation with LA-rich oils can increase muscle mass and decrease fat mass in adults. Unfortunately, many US dietary oils once high in LA are now high in oleic acid (OA) and low in LA, making it challenging for adults to increase LA intake. This study examines the extent in which consumption of healthy cookies enriched with LA for two weeks can increase plasma, erythrocytes and peripheral blood mononuclear cells (PBMC) LA levels. Methods: In a randomized double-blinded placebo-controlled study, healthy adults ( N = 84) were randomly assigned to consume one healthy cookie rich in LA or one healthy cookie rich in OA (placebo) per day for two weeks. The healthy cookies were high in unsaturated fat with 10 grams of either grapeseed oil (high in LA) or safflower oil (high in OA). Additionally, the healthy cookies were 100% whole grain and had about one half the amount of added sugar compared to traditional cookie recipes. Fasting blood was taken before (pre) and after (post) healthy cookie consumption. Fatty acids in the plasma, erythrocytes and PBMC were analyzed using gas chromatography. Because LA supplementation has been shown to reduce inflammation, plasma levels of total and high molecular weight (HMW) adiponectin and tumor necrosis factor receptor 2 (TNFr2) were assessed. A t-test of post values at a 5% significance level was used to determined differences between the two groups. Results: Of the 84 participants enrolled, 42 were randomly assigned to each group and all but one participant completed the study. 66% ( n = 55) of the participants were female. The mean age was 32.6 years and the mean BMI was 25.8. After two weeks of consuming one healthy cookie per day, LA was significantly higher in plasma, erythrocytes and PBMC in the group consuming the LA-rich healthy cookies compared to the group consuming the placebo healthy cookies. Levels of total and HMW adiponectin and TNFr2 were not different between the groups after healthy cookie consumption. Conclusions: Healthy cookies are a food-based approach to increasing LA in the diet that also alter the amount of LA in the blood. Future long-term studies are needed to assess the ability of healthy cookie consumption to alter body composition and markers of inflammation. Funding Sources: Funding was provided by the Carol S. Kennedy Professorship and the Ohio Agriculture Research and Development Center.